2014
DOI: 10.1037/a0036131
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences and age-related changes in divergent thinking in toddlers and preschoolers.

Abstract: Divergent thinking shows the ability to search for new ideas, which is an important factor contributing to innovation and problem solving. Current divergent thinking tests allow researchers to study children’s divergent thinking from the age of 3 years on. This article presents the first measure of divergent thinking that can be used with children as young as 2 years. The Unusual Box test is a nonverbal and nonimitative test in which children play individually with a novel toy and novel objects. Divergent thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 73 publications
5
55
0
Order By: Relevance
“…In the baseline condition, the experimenter (E) did not model any actions before handing the object to the child (C). The baseline condition followed the same procedure as the original UBT (Bijvoet‐van den Berg & Hoicka, ). In the Low Divergence/Low Activity condition, E modelled one action with each object once before handing it to C, for a total of five different actions across the study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the baseline condition, the experimenter (E) did not model any actions before handing the object to the child (C). The baseline condition followed the same procedure as the original UBT (Bijvoet‐van den Berg & Hoicka, ). In the Low Divergence/Low Activity condition, E modelled one action with each object once before handing it to C, for a total of five different actions across the study.…”
Section: Methodsmentioning
confidence: 99%
“…'s () procedure where only one action was modelled in the experimental conditions. As 2‐year‐olds produce on average 19.3 different actions in the UBT (with a standard deviation of 5.9, and a range of 10–32) (Bijvoet‐van den Berg & Hoicka, ), five actions were demonstrated per trial in the High Divergence condition. This resulted in a total of 25 different actions being shown to the children, a higher total than the average 2‐year‐old would invent themselves.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…DT is the ability to produce multiple solutions or ideas in response to a single problem or stimulus, such as generating alternative uses for a common object. Recent research has focused on DT of preschool children as young as two years old (Bijvoet‐van den Berg & Hoicka, ) and concluded that individual differences in DT start emerging during preschool age, and then, DT performance tends to increase. This general trend seems to continue until about age 40, followed by “systematic maturational declines” (McCrae, Arenberg, & Costa, ; p. 136), and is punctuated by multiple patterns of discontinuity, especially during childhood and adolescence.…”
Section: Discontinuity Of the Development Of Creative Potentialmentioning
confidence: 99%